Consecuencias de emplazar a sujetos procesales que no tienen legitimidad para obrar pasiva en los Procesos Contenciosos Administrativos en el Segundo Juzgado de Trabajo de Ascope del año 2009 al 2011 - Chamay Urquiza, Juana Consuelo (2017)
This thesis studies with rigor the consequences generated by placing procedural subjects who have no legitimacy to act passively in the Contentious Administrative Proceedings in the Second Specialized Permanent Labor Court of Ascope of the year 2009 to 2011, as in judicial practice in the aforementioned judged which is supported of the Local Education Management Unit of Ascope, Regional Management La Libertad and Public Prosecutor of the Regional Government La Libertad, without question, if legally they all have passive legitimacy to act in such processes. In this investigation it has been revised ninety six cases investigated in the Second Specialized Permanent Labor Court of Ascope of the Superior Court of Justice of La Libertad in the years 2009 to 2011; as well as survey has been applied to judges of the Superior Court of Justice of La Libertad who know administrative proceedings. This last one with the purpose to determine the way how to handle the Processes Contentious Administrative, such as the emplaced ones which are involved in these, and the consequences generated by admitting the intervention of procedural subjects that would not be called by law to defend the interests of the state. This led us as a result, that being the Regional Public Prosecutor who exercises the judicial defense of the interests of the regional governments, should be the only one to intervene as a defendant in the administrative proceedings; otherwise, the consequences generated by placing to procedural subjects who have no legitimacy to act passively in the administrative proceedings are the violation of the principles of equality, swiftness and procedural economy, which undoubtedly causes the increased load of procedures unnecessary for the Second Labor Court of Ascope.